An optochemical tool for light-induced dissociation of adherens junctions to control mechanical coupling between cells - Ollech, Dirk; Pflästerer, Tim; Shellard, Adam; Zambarda, Chiara; Spatz, Joachim P.; Marcq, Philippe; Mayor, Roberto; Wombacher, Richard; Cavalcanti-Adam, Elisabetta A. (Nature Communications, 2020)
The cadherin-catenin complex at adherens junctions (AJs) is essential for the formation of cell-cell adhesion and epithelium integrity; however, studying the dynamic regulation of AJs at high spatio-temporal resolution remains challenging. Here we present an optochemical tool which allows reconstitution of AJs by chemical dimerization of the force bearing structures and their precise light-induced dissociation. For the dimerization, we reconstitute acto-myosin connection of a tailless E-cadherin by two ways: direct recruitment of α-catenin, and linking its cytosolic tail to the transmembrane domain. Our approach enables a specific ON-OFF switch for mechanical coupling between cells that can be controlled spatially on subcellular or tissue scale via photocleavage. The combination with cell migration analysis and traction force microscopy shows a wide-range of applicability and confirms the mechanical contribution of the reconstituted AJs. Remarkably, in vivo our tool is able to control structural and functional integrity of the epidermal layer in developing Xenopus embryos.
Gesehen am 18.08.2020